The Effect of Student Team Achievement Division to Improve Students’ Reading Comprehension for the 10th Grade of SMAN 5 Kabupaten Tangerang - Siti Sopiyah; Isnaniah Isnaniah (English Education, Linguistics, and Literature Journal, 2023)
The purpose of this research is to find out the effect of using STAD (Student Team Achievement Division) to Improve Student’ Reading Comprehension for the tenth grade of SMAN 5 Kabupaten Tangerang. This research was quantitative and the method is quasi experimental with the qualitative data. In this research the total of population is 403 students in the tenth grade of SMAN 5 Kabupaten Tangerang. To choose the sample of this research the writer conducted by using the purposive sampling, and took 71 students of two classes, there are: the first is experimental class (X MIPA 1) and the second is control class (X MIPA 2). The STAD technique used in experimental class in teaching and learning process, while LM technique used in control class in teaching and learning process. To collect the data, the writer used the written test, and to counting the data of descriptive data of class experiment and control, normality, homogeneity, chi-square, rank, and mann whitney used SPSS 24. Then the result of this research showed the score of students’ reading comprehension that used STAD technique in the value of post-test was higher than the student’ score of reading comprehension that used LM technique in the value of post-test. In conclusion, in this research indicated that there is any significant effect of using STAD (Student Team Achievement Division) to improve student’ reading comprehension